2021
DOI: 10.1101/2021.12.20.21268130
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Rate of Asymptomatic Carriage Associated with Variant Strain Omicron

Abstract: The early widespread dissemination of Omicron indicates the urgent need to better understand the transmission dynamics of this variant, including asymptomatic spread among immunocompetent and immunosuppressed populations. In early December 2021, the Ubuntu clinical trial, designed to evaluate efficacy of the mRNA-1273 vaccine (Moderna) among persons living with HIV (PLWH), began enrolling participants. Nasal swabs are routinely obtained at the initial vaccination visit, which requires participants to be clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 8 publications
5
95
3
1
Order By: Relevance
“…All retested samples showed amplification of orf1a/b and S gene dropout in the TaqPath multiplex assay, suggestive of Omicron VoC as previously described 21 . However, we also observed an unusual N-gene dropout or Ct value shift in most of the samples with the TaqPath assay.…”
Section: ) a Ledsupporting
confidence: 65%
“…All retested samples showed amplification of orf1a/b and S gene dropout in the TaqPath multiplex assay, suggestive of Omicron VoC as previously described 21 . However, we also observed an unusual N-gene dropout or Ct value shift in most of the samples with the TaqPath assay.…”
Section: ) a Ledsupporting
confidence: 65%
“…Conversely, another potential bias could be systematic differences between the variants among non-diagnosed cases. For example, Omicron infections may have a higher rate of asymptomatic carriage than other variants of concern [ 13 ]. Such infections may be less likely to be diagnosed, which could result in an underestimation of the true reduction in risk of hospitalisation for Omicron compared with Delta.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they are not counted in the total tally. While studying the transmission dynamics of Omicron in immunocompetent and immunosuppressed populations, it was found that in comparison to other VOCs, asymptomatic carriage is increased to 16% in both people living with HIV and people living with HIV/AIDS in comparison to 2.6% during the Beta and Delta outbreaks ( Garrett et al, 2022 ).…”
Section: Is Previous Sars-cov-2 Infection Increase Susceptibility To Omicron?mentioning
confidence: 99%